Macrogeographic genetic structure of Lutzomyia longipalpis complex populations using Next Generation Sequencing - Casaril, Aline Etelvina; Alonso, Diego Peres [UNESP]; Franco, Karina Garcia; Niz Alvarez, Marcus Vinicius [UNESP]; Gomes Barrios, Suellem Petilim; Fernandes, Wagner de Souza; Moura Infran, Jucelei de Oliveira; Moura Rodrigues, Ana Caroline; Martins Ribolla, Paulo Eduardo [UNESP]; Oliveira, Alessandra Gutierrez de (Public Library Science, 2019)
Lutzomyia longipalpis is the main vector of Leishmania infantum, the causative agent of visceral leishmaniasis in the Neotropical realm. Its taxonomic status has been widely discussed once it encompasses a complex of species. The knowledge about the genetic structure of insect vector populations helps the elucidation of components and interactions of the disease ecoepidemiology. Thus, the objective of this study was to genotypically analyze populations of the Lu. longipalpis complex from a macrogeographic perspective using Next Generation Sequencing. Polymorphism analysis of three molecular markers was used to access the levels of population genetic structure among nine different populations of sand flies. Illumina Amplicon Sequencing Protocol' was used to identify possible polymorphic sites. The library was sequenced on paired-end Illumina MiSeq platform. Significant macro geographical population differentiation was observed among Lu. longipalpis populations via PCA and DAPC analyses. Our results revealed that populations of Lu. longipalpis from the nine municipalities were grouped into three clusters. In addition, it was observed that the levels of Lu. longipalpis population structure could be associated with distance isolation. This new sequencing method allowed us to study different molecular markers after a single sequencing run, and to evaluate population and inter-species differences on a macrogeographic scale.